Dari konkret ke virtual: mengembangkan LKPD problem-based learning berbantuan cabri 3D sebagai jembatan peningkatan kompetensi pemecahan dan komunikasi matematis siswa - Sapyuddin Shaf; Tri Dyah Prastiti; Mery Noviyanti (International Journal of Progressive Mathematics Education, 2025)
Purpose: This research develops a Problem-Based Learning (PBL) Student Worksheet (LKPD) assisted by Cabri 3D software to address students' low mathematical communication and problem-solving abilities caused by conventional teaching models and a lack of innovative materials. Design/methodology/approach: Employing the Research and Development (R&D) method with the Plomp model (preliminary investigation, prototype development, and assessment phases) and Tessmer’s formative evaluation design, this study involved ninth-grade students at SMP Negeri 5 Tinambung. Data were gathered through expert validation, questionnaires, observations, and pretest-posttest measurements, then analyzed descriptively and inferentially. Findings: Results indicate that the developed LKPD meets the criteria of being highly valid, highly practical, and effective. The field trials demonstrated a significant improvement in both students’ mathematical communication and problem-solving abilities (Sig. 0.000 < 0.05). Practical implications: These findings provide educators with a validated, innovative instructional tool that strengthens the integration of dynamic geometry software (Cabri 3D) within a PBL framework to enhance interactive and analytical mathematics learning. Originality/value: The significance of this study lies in its specific and systematic integration of Cabri 3D technology within a PBL-based worksheet, offering a novel, interactive approach to simultaneously elevating both spatial-mathematical communication and complex problem-solving skills in junior high school geometry.   Purpose: Penelitian ini mengembangkan Lembar Kerja Peserta Didik (LKPD) berbasis Problem-Based Learning (PBL) berbantuan perangkat lunak Cabri 3D untuk mengatasi rendahnya kemampuan komunikasi matematis dan pemecahan masalah siswa akibat model konvensional dan minimnya bahan ajar inovatif. Design/methodology/approach: Menggunakan metode Penelitian dan Pengembangan (R&D) model Plomp (fase investigasi awal, pengembangan prototipe, dan penilaian) yang dipadukan dengan desain formative evaluation Tessmer, penelitian ini melibatkan siswa kelas IX SMP Negeri 5 Tinambung. Data dikumpulkan melalui validasi ahli, angket, observasi, serta tes awal-akhir (pretest-posttest), lalu dianalisis secara deskriptif dan inferensial. Findings: Hasil menunjukkan bahwa LKPD yang dikembangkan memenuhi kriteria sangat valid, sangat praktis, dan efektif. Uji coba lapangan membuktikan adanya peningkatan yang signifikan pada kemampuan komunikasi matematis dan pemecahan masalah siswa (Sig. 0,000 < 0,05). Practical implications: Temuan ini menyediakan bahan ajar inovatif yang tervalidasi bagi pendidik, yang memperkuat integrasi antara teknologi geometri dinamis (Cabri 3D) dan sintaks PBL untuk mewujudkan pembelajaran matematika yang lebih interaktif dan analitis. Originality/value: Keunggulan studi ini terletak pada integrasi sistematis teknologi Cabri 3D ke dalam LKPD berbasis PBL, memberikan pendekatan interaktif baru untuk secara bersamaan meningkatkan kemampuan komunikasi spasial-matematis dan keterampilan pemecahan masalah kompleks pada materi geometri di tingkat SMP.